PERAN MEDIA SOSIAL DALAM MEMPERKENALKAN BAKAL CALON MENJELANG PEMILIHAN UMUM LEGISLATIF 2019 DI KABUPATEN ACEH JAYA - Aminah Aminah (SOURCE : Jurnal Ilmu Komunikasi, 2018)
This research aims to explain about to examine about the role of social media in introducingbilled candidate ahead of the legislative election 2019 in the district of Aceh Jaya and theadvantages and disadvantages in the use of social media by every political actors of Aceh Jaya.The data that is required in writing is obtained through library research and field. Libraryresearch done with how to read text books, legislation, and other reading material related tothis research. While field research done by interviewing informants. The results of the studyshowed that social media has an important role in introducing the embryo candidate forlegislative members. Through social media particularly Facebook, the embryo candidate forlegislative members can promote itself faster, right and would not eat a large amount of moneyin campaigning. In addition, social media users there is no limits in campaigning. Anytime andanywhere during can still be reachable by internet network, so everyone can take advantage ofit. But despite this, social media also has a shortage of displays the existence of the party who isnot responsible to take photos to be made as a mock materials or arranged by these accountscrowd and distributed so that they can execute the popularity and elektabilitas from billedcandidate for legislative members.Key Words: The Role, Media, Political Communication and Legislative Election